Association between social determinants of health and olfactory function: a scoping review. Issue 10 (28th May 2021) - James, Joel; Tsvik, Avraham M.; Chung, Sei Y.; Usseglio, John; Gudis, David A.; Overdevest, Jonathan B.
Abstract: Background: Social determinants of health (SDoH) include the socioeconomic, demographic, and social conditions that influence differences in health status among individuals and groups. The impact of these conditions on olfactory function remains poorly understood. In this scoping review, we systematically review the available literature to synthesize the association between SDoH and olfactory function. Methods: In accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses extension for Scoping Review (PRISMA‐ScR) guidelines, we performed systematic search queries in PubMed, Embase, and Ovid databases and categorized articles according to themes that emerged regarding SDoH. The primary outcomes included self‐reported and objective measurements of smell. Results: We identified 722 unique references that underwent title and abstract review by two independent reviewers, with 70 articles undergoing full‐text review and 57 relevant for data extraction. Six themes emerged in our review, under which we categorized the studies and synthesized respective associations with olfactory function. These include studies exploring socioeconomic status (n = 19, 33%), education status (n = 27, 47%), occupational exposures (n = 26, 46%), racial/ethnic disparities (n = 12, 21%), and lifestyle/behavioral factors (n = 33, 58%). Conclusions: Within the context of this scoping review, olfactory dysfunction is significantly more prevalent in patients with lower socioeconomic status, exposure to environmental and occupational toxins, and of minority race/ethnicity, whereas the associations between olfactory dysfunction and education level and lifestyle factors such as smoking and drinking seem to be much more elusive. This review highlights the importance of accounting for SDoH in observational studies examining olfactory outcomes. Given the increased awareness of olfactory loss, special consideration should be given to understanding olfactory dysfunction in the context of these factors.